2009
DOI: 10.1590/s1678-77572009000700010
|View full text |Cite
|
Sign up to set email alerts
|

The maturational process of the auditory system in the first year of life characterized by brainstem auditory evoked potentials

Abstract: The study of brainstem auditory evoked potentials (BAEP) allows obtaining the electrophysiological activity generated in the cochlear nerve to the inferior colliculus. In the first months of life, a period of greater neuronal plasticity, important changes are observed in the absolute latency and inter-peak intervals of BAEP, which occur up to the completion of the maturational process, around 18 months of life in full-term newborns, when the response is similar to that of adults. Objective: The goal of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
11
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
11
11
2
3
Order By: Relevance
“…The results of the present study showed the lack of asymmetry between the ears in the evaluated groups, in contrast with a study that found higher wave V amplitude and lower BAEP wave latency in the right ear, suggesting that the right ear is favored in auditory processing along the auditory pathway (15) . Our results are consistent with the current literature, concluding that the maturational process along the central auditory pathways occurs simultaneously in both ears (16)(17)(18)(19) . During the neonatal period, the comparison between the AGA and SGA groups (Table 1) showed no differences, except for wave I, which was significantly more precocious in the AGA group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study showed the lack of asymmetry between the ears in the evaluated groups, in contrast with a study that found higher wave V amplitude and lower BAEP wave latency in the right ear, suggesting that the right ear is favored in auditory processing along the auditory pathway (15) . Our results are consistent with the current literature, concluding that the maturational process along the central auditory pathways occurs simultaneously in both ears (16)(17)(18)(19) . During the neonatal period, the comparison between the AGA and SGA groups (Table 1) showed no differences, except for wave I, which was significantly more precocious in the AGA group.…”
Section: Discussionsupporting
confidence: 93%
“…The preparation of all NBs for BAEP testing was conducted as follows: prior cleaning of the skin with abrasive paste and fixation of Kendal® Meditrace-200 disposable pediatric electrodes on the forehead (Fpz) and the right and left mastoids (M 2 and M 1 ), according to the International Electrode Systems standards (IES [10][11][12][13][14][15][16][17][18][19][20]. The acoustic stimulus was presented by a pair of ER-3A insertion earphones, eliciting the responses.…”
Section: Thismentioning
confidence: 99%
“…The auditory evoked potentials show some patterns associated with maturation in myelination of the auditory system (Amorim et al, 2009). Electrophysiological studies of the auditory system have demonstrated that maturation of the structures occurs from the periphery to the center, without following a hierarchical pattern (Eggermont and Ponton, 2003;Ponton et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies of the auditory system have demonstrated that maturation of the structures occurs from the periphery to the center, without following a hierarchical pattern (Eggermont and Ponton, 2003;Ponton et al, 2000). Thus, through BAEP, maturation of the auditory nerve and brain stem may be detected, and the occurrence of an abnormal developmental process may be verified (Amorim et al, 2009). Early waves obtained on BAEP correspond to the peripheral, whereas late waves correspond to the central auditory pathways (Rosenhall et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there may be contamination of electrical noise in the amplifier, both from the computer and the power grid (9) . Among the most cited clinical applications of ABR are the evaluation of auditory pathways of the brainstem in adults and the determination of the electrophysiological auditory threshold, especially in children, making ABR an essential exam within the procedures used for audiological diagnosis, particularly in pediatric clinic (10,11,12,13,14,15,16,17,18) . There are advantages and limitations in the clinical application and correct interpretation of ABR, which can be performed in infants, young children, and in patients difficult to evaluate.…”
Section: Introductionmentioning
confidence: 99%